BRISMES 1994 Annual Conference - Abu-Bakr M. Asmal (International Institute of Islamic Thought, 1994)
The annual conference of the British Society for Middle Eastern Studies (BRISMES) was hosted by the Department of Middle Eastern Studies at the University of Manchester and concentrated on the theme of "Culture: Unity and Diversity." About two hundred participants deliberated over approximately ninety papers of varying standards, in addition to the three plenary sessions. This was achieved by grouping the speakers, many of whom were from overseas, into thirty-four panels covering such diverse themes as law, politics, language, literature, poetry, culture, identity, history, religion, architecture, mysticism, media, economics, and agriculture. A balance was also maintained between the historical and the contemporary in many of these areas. Each session. featured up to five panels, each with between two and four speakers. These were held simultaneously in order to give all of the participants in each session the opportunity to choose the one panel that would be of most interest to them. Some of the panels were hosted by special interest groups: The Society for Moroccan Studies; The Association for Cypriot, Greek and Turkish Affairs; The Manchester University Research Group on Central Asia and the Caucasus; and two panels in memory of Avriel Butovsky. The focus of the conference's attention was the plenary session on each of the three days. A different guest speaker was present for each session. The most striking presentation was that of Seyyed Hossein Nasr (George Washington University, USA). The opening plenary address was by Bozkurt Guvem; (Ankara, Turkey), and the closing plenary session featured Tayeb Salih (London, UK). After the opening speeches, Bozkurt Guven????. currently advisor to the President of Turkey and formerly an anthropologist and architect, was called upon to speak on the "Quest for National Identity in Turkey: Cultural Continuity of Historical Diversities." He began by focusing on the dilemma that a quest for identity generates due to its deep-rootedness in the sociocultural and historical consciousness of people at the individual, collective, local, national, static, and transitional levels. In answer to the question "Who are you?," one's identity is as much dependent on the attitude of the perceiver as it is on the perception that the perceived has of himself or herself. It is therefore ...